Latency Analysis of TCP on an ATM Network - Wolman, Alec; Voelker, Geoffrey M.; Thekkath, Chandramohan A. (WTEC'94 Proceedings of the USENIX Winter 1994 Technical Conference, 1994)
In this paper we characterize the latency of the BSD 4.4 alpha implementation of TCP on an ATM network. Latency reduction is a difficult task, and careful analysis is the first step towards reduction. We investigate the impact of both the network controller and the protocol implementation on latency. We find that a low latency network controller has a significant impact on the overall latency of TCP. We also characterize the impact on latency of some widely discussed improvements to TCP, such as header prediction and the combination of the checksum calculation with data copying.